The miracle & tragedy of the Dionne quintuplets - Miller, Sarah, 1979- (Schwartz & Wade Books, 2019)
"When they were born on May 28, 1934, quintuplets Yvonne, Annette, Cécile, Émilie, and Marie captivated the world, defying medical history with every breath they took. In an effort to protect them from hucksters and showmen, the Ontario government took custody of the quints, sequestering them in a private, custom-built hospital across the road from their family. Here, Sarah Miller reconstructs their unprecedented upbringing with depth and subtlety, illustrating not only their resilience, but also the unique bond of their sisterhood"--